Syrian Crisis in the Context of Emerging Multipolar International Order - M. S. Khodynskaya-Golenischeva (Vestnik MGIMO-Universiteta)
The article looks into the Syria crisis in the context of emerging multipolar, polycentric system of international relations. The author focuses on Washington's attempts to maintain its dominance in world affairs by any means, by consciously destabilizing political situations in certain countries to weaken them and then act according to the "divide and rule" principle. Syria is no exception. In this context, the author lists methods implied before in a number of specific regions aimed at destabilizing situations in different countries and describes specific objectives that the US and its allies are seeking to achieve thereby. The author also shows how these methods have been used in Syria. At the same the article says that objective trends in the world system, including emergence of new centers of political and economic power and, as a consequence, formation of a democratic multi-dimensional system of international relations, lead to a situation when the methods used by Washington to destabilize internal political situations, cease to work properly. The most powerful levers of political, economic, financial and informational pressure lose their effectiveness. In the case of Syria, the new political realities literally "squeezed" Washington into political and legal sphere, and instead of US bombardment of Syria the world saw an agreement on the destruction of Syrian chemical weapons which was carried out under international community control. It is emphasized that these trends will only be strengthened, and multipolar world order will gradually neutralize new Western attempts to destabilize regions for gaining geopolitical advantage. This in turn gives a chance to create an atmosphere for a process of finding a comprehensive political solution to the crisis in Syria, which Russia is currently making efforts to launch.